Influence of Annealing Methods on the Magnetic Properties and Flexural Strength of Iron-OER Soft Magnetic Composites - Ling Xiao; Ming Li; Wenjie Cheng; Hongwei Fan; Xingzhou Chen; Yanhua Sun; Chunhua Ding; Lie Yu (Advances in Materials Science and Engineering)
This study aims at investigating high flexural strength iron-OER soft magnetic composites (SMCs) for active magnetic bearings (AMBs). Iron powders were firstly coated with oxide layer by the passivation process at room temperature. The effect of annealing methods on the static performance, magnetic properties, and flexural strength of SMCs was studied. The results showed that the significant improvements of permeability, magnetic loss, and flexural strength were presented by increasing the bonding number between iron surface and resin and using the two-step annealing method. In addition, the effect of pore shape and angle on the behavior of material fracture has been studied by FEM and the analysis was validated by experimental results.